New Innovations in Engineering Education and Naval Engineering - Sayeed Hassan, Nur Md; António Neves Lousada, Sérgio (IntechOpen, 2020)
This book, Naval Engineering, comprises information on different interdependent technical aspects important in the development of a ship project in its entirety.Part One of this book introduces cutting edge research on the key issues of the latest advances in developing a successful engineering curriculum, in designing an innovative learning and teaching method, and in promoting consistent standards in engineering education. Part Two provides a wider perspective in the area of naval engineering and presents its relevant challenges and new opportunities. The chapters included in this book cover the related concepts of technical, sustainable, and social innovation that have a substantial influence on the society and the stakeholders. This book intends to provide a wider perspective for the naval engineering field. It presents relevant challenges, as well as new opportunities.